Segmentation and classification of individual clouds in images captured with horizon-aimed cameras for nowcasting of solar irradiance absorption - Martins, Bruno Juncklaus (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2024.